FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PADA KOPERASI TIRADANA SURABAYA - Nengke, Hugo; Estiasih, Soffia Pudji (Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of this study was to analyze the positive and significant influence between credit regulations, working capital, and the number of service user members on income at the Tirtadana Cooperative in Surabaya. The population in this study are the members and creditors in the Tirtadana Surabaya cooperative with a sample designation of 55 respondents, this test was carried out with a significant level of 0.05. The analytical tool used in this study is multiple linear regression, where the resulting equation is Y = 0.981 + 0.206X1 + 0.872X2 + 0.448X3. The results of the study using the t test, that partially credit regulations, working capital, and the number of service user members have a positive and significant effect on cooperative income, where the significance value of each variable is less than the significant value of 0.05. The results of the study using hypothesis testing with the F test (simultaneous), showed that simultaneous credit regulation, working capital and the number of service user members together had a positive and significant effect on the income of the Tirtadana cooperative. The magnitude of the effect of credit regulations, working capital, and the number of service user members on income at the Tirtadana cooperative in the city of Surabaya is 92.1%. Keywords: Credit Regulation, Working Capital, Number of Service User Members and Cooperative Revenues